Visual arts for the inclusion of sexual diversity in the training of elementary education teachers (Revista Apotheke, 2023)
In this article we highlight the need to train elementary school teachers in the field of sexual diversity. The main objective is to find out to what extent future elementary school teachers are receiving this type of training, subsequently presenting proposals to improve this precarious training situation that exists regarding the inclusion of sexual and gender dissent in schools. Among the secondary objectives we highlight the need to use attractive tools to deal with these issues in the classroom. We observed that, in relation to sexual diversity, Visual Arts and Art/Education[1] offer us the opportunity to incorporate images, works and artists who work on these issues, for which we use the Museari virtual museum as a support tool. We use the case study methodology. After incorporating these actions into classes, a questionnaire was prepared in which all participants responded. When analyzing the results, the conclusion we reached is that the training experience in sex-gender diversity and inclusion has been interesting and innovative for them, having encouraged reflection on how to incorporate these issues into the dynamics of the elementary school classroom. [1] We chose the terminology Art/Education instead of Artistic Education.
Keywords: art; education; sexual diversity; museums; teacher training